Between Secularization and Post-Secularism – on Disenchantment of the World from the Perspective of the Sociology of Religion - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
This article reviews the most representative, relevant findings for the sociology of religion, which may serve as a valid context for the theory of religion developed at the same time by Erich Fromm. The conclusions arising from the review are then applied to the question of the validity of the diagnosis of the disenchanted world.
Keywords: secularization; post-secularism; sociology of religion